Integrated Bi‐Layered Scaffold for Osteochondral Tissue Engineering. Issue 6 (6th December 2012) - Galperin, Anna; Oldinski, Rachael A.; Florczyk, Stephen J.; Bryers, James D.; Zhang, Miqin; Ratner, Buddy D.
Abstract Osteochondral tissue engineering poses the challenge of combining both cartilage and bone tissue engineering fundamentals. In this study, a sphere‐templating technique was applied to fabricate an integrated bi‐layered scaffold based on degradable poly(hydroxyethyl methacrylate) hydrogel. One layer of the integrated scaffold was designed with a single defined, monodispersed pore size of 38 μm and pore surfaces coated with hydroxyapatite particles to promote regrowth of subchondral bone while the second layer had 200 μm pores with surfaces decorated with hyaluronan for articular cartilage regeneration. Mechanical properties of the construct as well as cyto‐compatibility of the scaffold and its degradation products were elucidated. To examine the potential of the biphasic scaffold for regeneration of osteochondral tissue the designated cartilage and bone layers of the integrated bi‐layered scaffold were seeded with chondrocytes differentiated from human mesenchymal stem cells and primary human mesenchymal stem cells, respectively. Both types of cells were co‐cultured within the scaffold in standard medium without soluble growth/differentiation factors over four weeks. The ability of the integrated bi‐layered scaffold to support simultaneous matrix deposition and adequate cell growth of two distinct cell lineages in each layer during four weeks of co‐culture in vitro in the absence of soluble growth factors was demonstrated.